2019
DOI: 10.1039/c9nr03793d
|View full text |Cite
|
Sign up to set email alerts
|

Optical cooling of lead halide perovskite nanoparticles enhanced by Mie resonances

Abstract: A novel strategy for the enhancement of optical cooling at the nanoscale based on optical resonance engineering in halide perovskite nanoparticles is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…One of the possible applications of the Purcell factor enhancement in perovskite nanoparticles is more efficient optical cooling at the nanoscale. Indeed, as was predicted theoretically 89 , this effect helps to boost internal QY of PL for MAPbI 3 nanoparticles and enhance the absorption of light at pumping wavelength below band gap. As a result, we may expect the cooling down to ∆T ≈-100 K.…”
Section: Holographic Luminescent or Lasing Imagessupporting
confidence: 61%
See 1 more Smart Citation
“…One of the possible applications of the Purcell factor enhancement in perovskite nanoparticles is more efficient optical cooling at the nanoscale. Indeed, as was predicted theoretically 89 , this effect helps to boost internal QY of PL for MAPbI 3 nanoparticles and enhance the absorption of light at pumping wavelength below band gap. As a result, we may expect the cooling down to ∆T ≈-100 K.…”
Section: Holographic Luminescent or Lasing Imagessupporting
confidence: 61%
“…4b,f,j). Taking into account spontaneous emission acceleration via the Purcell effect, the internal QY can be modified as following 89 :…”
Section: Photoluminescence and Lasingmentioning
confidence: 99%
“…Nanostructured lead halide perovskite materials have gained significant attention in the last few years mainly because of their potential for application in the field of electronics and photonics. There are several available reports demonstrating their implementation into light emitting diodes (LED) 1 3 , solid-state lasers 4 , solar cells 5 , photodetectors 6 and optical cooling systems 7 . Especially the photoluminescence quantum yields (PLQY) of up to 100% make these nanostructured perovskite materials very interesting 8 .…”
Section: Introductionmentioning
confidence: 99%
“…13b). [184] In this case, the expression for the temperature variance inside the NP can be found by solving the equation for thermal diffusion and appears to be following:…”
Section: Optical Coolingmentioning
confidence: 99%
“…The numerical and analytical modeling revealed that the highest cooling efficiencies for a halide perovskite spherical NP correspond to the excitation of magnetic-type Mie modes. [184] Namely, magnetic octupole at the emission and magnetic quadrupole at absorption allow for cooling a single nanocavity by ∆T ≈ -110 K at realistic conditions. In opposite, GaAs nanoparticles with less efficient PL can not be optically cooled with this mechanism as shown in Fig.…”
Section: Optical Coolingmentioning
confidence: 99%